Septic arthritis of the temporomandibular joint as a complication of acute otitis media in a child: A rare case and the importance of real-time PCR for diagnosis. Issue 11 (November 2015) - Bast, F.; Collier, S.; Chadha, P.; Collier, J.
Abstract We document the case of a 7-year-old boy who presented with pain in his left ear and trismus after a diagnosis of acute otitis media one week previously. His blood inflammatory markers were raised and magnetic resonance imaging (MRI) showed significant left temporomandibular joint effusion and partial attenuation of the left mastoid. A clinical diagnosis of septic arthritis of the TMJ was made and the patient was commenced on broad-spectrum antibiotics. Analysis using real time PCR enabled identification of the offending organism, confirmation of the diagnosis and antibiotic treatment to be specifically tailored for treatment.